Birds of a Feather Resist Together: Sociality and Species Predict the Resilience and Recovery Strategies of Two Neotropical Birds - Melissa Ardila‐Villamizar; Daniela T. Sandoval; Adriana A. Maldonado‐Chaparro (Ecology and Evolution)
ABSTRACT Behavioral resilience—the ability of animals to recover from disturbances—offers a valuable measure of how urban dwellers cope with human‐induced disturbances. In this study, we conducted behavioral trials across six study sites varying in urbanization level in Bogota, Colombia to assess the resilience and behavioral strategy that great thrushes (Turdus fuscater) and eared doves (Zenaida auriculata) employed to achieve it (i.e., recovery strategies). During the trials we measured initial escape responses (flight initiation distance or FID, and alert distance or AD), exposed individuals to a simulated disturbance (human running), and subsequently assessed whether, after the disturbance, they resumed foraging and/or changed their behavior along with their displacement to foraging patches. We also examined the influence of ecological factors such as distance to escape cover, microhabitat, urbanization, flock size, and species in both resilience and the recovery strategies of focal individuals. Our results showed that while most individuals were not resilient, sociality significantly enhanced resilience, with birds in larger flocks more likely to habituate to disturbances. Other factors, such as distance to escape cover, urbanization level and microhabitat did not influence the resilience or strategies employed by individuals. While avoidance was the primary recovery strategy, individuals also reduced their responsiveness, increased vigilance, or adopted a wait and see approach in response to the disturbance. These findings underscore the importance of social behavior and behavioral flexibility in shaping the resilience of urban birds to human disturbance.